Viabilitas Awal, Daya Simpan dan Invigorasi Benih Kemangi (Ocimum basilicum L.) - Suwarno, Faiza Chairani; Sari, Maryati; Manggung, Raden Enen Rindi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTBasil (Ocimum basilicum L.) is cultivated in many countries as vegetable crop, and as herbal medicine or pesticide for mosquito larvae, but there is limited information on its seed viability. Three experiments were conducted at Seed Science and Technology Laboratory Departement of Agronomy and Horticulture IPB from January to June 2011. Experiment one tested viability of basil seeds with different maturation obtained from different fruit maturity and drying treatment. Experiment two stored basil seed for 12 weeks in ambient condition and tested seed viability weekly. In experiment three, two seed lots that have been stored for 2 and 14 weeks in ambient condition were invigorated with GA3 1,000 ppm and KH2PO4 1.5% and light treatment 820 lux m-2. It was revealed that basil seed was physiologically mature at 44-49 days after flowering with 12.5% moisture content and low viability of 34.0%. After-ripening period of basil seed was two week where the seed viabilty increase to 56.7%. Seed viability did not significantly change during 12 weeks stored in ambient condition. Maximum viability of basil seed (64.34-66.52%) could be achieved by invigoration treatment with GA3 1,000 ppm and light treatment 820 lux m-2.Keywords: dormancy, germination, seed maturity, vegetable crop